2020
DOI: 10.1111/apa.15348
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis found that intranasal dexmedetomidine was a safe and effective sedative drug during paediatric procedural sedation

Abstract: Aim This systematic review and meta‐analysis evaluated the effectiveness of intranasal dexmedetomidine as a sole sedative during paediatric procedural sedation outside the operating room. Methods Relevant literature identified by PubMed, Scopus, ClinicalTrials.gov, ScienceDirect and Cochrane Library up to 31 December 2019 was systematically reviewed. Randomised controlled trials that compared intranasal dexmedetomidine with another sedative or placebo during paediatric procedural sedation were included. Trials… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 42 publications
0
22
0
Order By: Relevance
“…Further inquiry would be necessary to understand why a quarter of children do not have access to N 2 O, a question this survey did not address. Intranasal dexmedetomidine has been gaining adoption in the recent years [ 25 29 ], as an efficacious alternative to midazolam for non-painful procedures, with the added advantage, of not being painful during administration unlike midazolam [ 30 ], its effects mimicking sleep, being safe [ 31 ], and being protective in anesthetic neurotoxicity [ 32 34 ]. Its availability to only one tenth of the children represented by our study appears reflective of only a slow rise in popularity, perhaps secondary to a longer onset and duration of action than midazolam, which makes it less useful in environments where throughput is important, or secondary to physician familiarity and preference for older medications such as midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…Further inquiry would be necessary to understand why a quarter of children do not have access to N 2 O, a question this survey did not address. Intranasal dexmedetomidine has been gaining adoption in the recent years [ 25 29 ], as an efficacious alternative to midazolam for non-painful procedures, with the added advantage, of not being painful during administration unlike midazolam [ 30 ], its effects mimicking sleep, being safe [ 31 ], and being protective in anesthetic neurotoxicity [ 32 34 ]. Its availability to only one tenth of the children represented by our study appears reflective of only a slow rise in popularity, perhaps secondary to a longer onset and duration of action than midazolam, which makes it less useful in environments where throughput is important, or secondary to physician familiarity and preference for older medications such as midazolam.…”
Section: Discussionmentioning
confidence: 99%
“…[ 30 ] Furthermore, it has little effect on circulatory function and no respiratory depression. [ 31 ] Previous study [ 32 ] has showed that sedation with dexmedetomidine can significantly reduce the incidence of delirium after surgery. Postoperative PCEA can effectively slow the conduction of low-level sympathetic nerves, and block the transmission of noxious stimuli to the central nervous system, significantly reduce the release of inflammatory factors, and reduce the damage of inflammatory factors to the central nervous system.…”
Section: Discussionmentioning
confidence: 99%
“…Dexmedetomidine continues to be described as a novel drug, yet emerging literature suggests its favourable role in paediatric procedural sedation with IN delivery. 2,3 In the paediatric setting, it may produce a higher procedural completion rate than midazolam with a similarly low complication rate when used as a sole sedative. 2 Similar has been found in the paediatric population when used as a pre-medication.…”
Section: Discussionmentioning
confidence: 99%
“…3 It has an estimated sedation onset time of 16.9 min (± 2.6 min) and an estimated duration of sedation of 81.5 min (±4.8 min) with 1-3 mcg/kg doses. 2 More profound and longer sedation is seen with higher doses. 2 In a small study of healthy young adults, estimated sedation onset time was 47.5 min (25-135 min).…”
Section: Role In Procedural Sedationmentioning
confidence: 99%
See 1 more Smart Citation